Unilateral prurigo nodularis: a rare presentation - Bhatia, Kailash; Kataria, Rajesh; Parekh, Niyati; Kothari, Jayesh; Kumar, Ravindra (International Journal of Research in Medical Sciences, 2017)
Prurigo Nodularis (PN) is a rare chronic skin disorder of unknown etiology. Here we are describing a case of 14 year old girl having prurigo nodularis with no other systemic illness.